Zebrafish mafbb Mutants Display Osteoclast Over-Activation and Bone Deformity Resembling Osteolysis in MCTO Patients - Yujie Han; Weihao Shao; Dan Zhong; Cui Ma; Xiaona Wei; Abrar Ahmed; Tingting Yu; Wei Jing; Lili Jing (Biomolecules, 2021)
Multicentric carpotarsal osteolysis (MCTO) is a rare skeletal dysplasia with osteolysis at the carpal and tarsal bones. Heterozygous missense mutations in the transcription factor MAFB are found in patients with MCTO. MAFB is reported to negatively regulate osteoclastogenesis in vitro. However, the in vivo function of MAFB and its relation to MCTO remains unknown. In this study, we generated zebrafish MAFB homolog mafbb mutant utilizing CRISPR/Cas9 technology. Mafbb deficient zebrafish demonstrated enhanced osteoclast cell differentiation and abnormal cartilage and bone development resembling MCTO patients. It is known that osteoclasts are hematopoietic cells derived from macrophages. Loss of mafbb caused selective expansion of definitive macrophages and myeloid cells, supporting that mafbb restricts myeloid differentiation in vivo. We also demonstrate that MAFB MCTO mutations failed to rescue the defective osteoclastogenesis in mafbb−/− embryos, but did not affect osteoclast cells in wild type embryos. The mechanism of MCTO mutations is likely haploinsufficiency. Zebrafish mafbb mutant provides a useful model to study the function of MAFB in osteoclastogenesis and the related MCTO disease.